Effect of Inoculation of VAM Fungi and Rhizobium on Growth and Biomass Production in Acacia nilotica in Nursery - Verma, R. K.; , Jamaluddin; Gupta, B. N. (Indian Forester, 1994)
Seedlings of Acacia nilotica were inoculated with Rhizobium strain, isolated from nodules of the same species, VAM fungi and single dose of nitrogen and phosphorus in unsterilized soil in nursery condition. A single species of VAM fungus, Glomus mosseae and a mixture of VAM fungi locally isolated, consisting of Glomus species and a Gigaspora sp. Were used to inoculate the seedlings. Height growth, collar diameter, nodulation, percentage root infection by VAM fungi, fresh and dry weights of shoot and roots were determined after 4 months of inoculation. Inoculation of Rhizobium and VAM fungi and application of nitrogen and phosphorus singly or in different combinations enhanced the growth and biomass production as compared to uninoculated (control) seedlings. Maximum seedlings volume (height x root collar diameter2) was found in seedlings inoculated with G. mosseae and Rhizobium in combination, as well as Rhizobium and phosphorus combination followed by mixed inoculum of VAM fungi. Maximum total dry biomass was recorded in seedlings treated with a combination of mixture of VAM fungi, Rhizobium VAM mixed and phosphorus. It is concluded that inoculation of VAM fungi, Rhizobium singly or in combination is equally or more beneficial over use of chemical fertilizers in raising the seedlings of Acacia nilotica.